Biofortification of Broccoli Microgreens (Brassica oleracea var. italica) with Glucosinolates, Zinc, and Iron through the Combined Application of Bio- and Nanofertilizers - Carlos Esteban Guardiola-Márquez; C. Valentina García-Sánchez; Óscar Armando Sánchez-Arellano; Erika Melissa Bojorquez-Rodríguez; Daniel A. Jacobo-Velázquez (Foods, 2023)
There is a severe need to develop a sustainable, affordable, and nutritious food supply system. Broccoli microgreens have attracted attention due to their rich nutritional content and abundant bioactive compounds, constituting an important opportunity to feed the ever-increasing population and fight global health problems. This study aimed to measure the impact of the combined application of biofertilizers and zinc and iron nanofertilizers on plant growth and the biofortification of glucosinolates (GLSs) and micronutrients in broccoli microgreens. Biofertilizers were based on plant growth-promoting (PGP) bacterial consortia previously isolated and characterized for multiple PGP traits. Nanofertilizers consisted of ZnO (77 nm) and γ-Fe2O3 (68 nm) nanoparticles synthesized with the coprecipitation method and functionalized with a Pseudomonas species preparation. Treatments were evaluated under seedbed conditions. Plant growth parameters of plant height (37.0–59.8%), leaf diameter (57.6–81.1%) and fresh weight (112.1–178.0%), as well as zinc (122.19–363.41%) and iron contents (55.19–161.57%), were mainly increased by nanoparticles subjected to the functionalization process with Pseudomonas species and uncapped NPs applied together with the biofertilizer treatment. Regarding GLSs, eight compounds were detected as being most positively influenced by these treatments. This work demonstrated the synergistic interactions of applying ZnO and γ-Fe2O3 nanofertilizers combined with biofertilizers to enhance plant growth and biofortify micronutrients and glucosinolates in broccoli microgreens.